Evidence for speciation underground in diving beetles (Dytiscidae) from a subterranean archipelago. (1st January 2021) - Langille, Barbara L.; Hyde, Josephine; Saint, Kathleen M.; Bradford, Tessa M.; Stringer, Danielle N.; Tierney, Simon M.; Humphreys, William F.; Austin, Andrew D.; Cooper, Steven J. B.
Abstract: Most subterranean animals are assumed to have evolved from surface ancestors following colonization of a cave system; however, very few studies have raised the possibility of "subterranean speciation" in underground habitats (i.e., obligate cave‐dwelling organisms [troglobionts] descended from troglobiotic ancestors). Numerous endemic subterranean diving beetle species from spatially discrete calcrete aquifers in Western Australia (stygobionts) have evolved independently from surface ancestors; however, several cases of sympatric sister species raise the possibility of subterranean speciation. We tested this hypothesis using vision (phototransduction) genes that are evolving under neutral processes in subterranean species and purifying selection in surface species. Using sequence data from 32 subterranean and five surface species in the genus Paroster (Dytiscidae), we identified deleterious mutations in long wavelength opsin ( lwop ), arrestin 1 ( arr1 ), and arrestin 2 ( arr2 ) shared by a sympatric sister‐species triplet, arr1 shared by a sympatric sister‐species pair, and lwop and arr2 shared among closely related species in adjacent calcrete aquifers. In all cases, a common ancestor possessed the function‐altering mutations, implying they were already adapted to aphotic environments. Our study represents one of the first confirmed cases of subterranean speciation in cave insects. The assessment of genes undergoing pseudogenization provides a novel way of testing modes of speciation and the history of diversification in blind cave animals.